Reaction of Pertechnetate in Highly Alkaline Solution: Synthesis and Characterization of the Nitridotrioxotechnetate Ba[TcO3N]. Issue 63 (12th September 2022) - Badea, D.; Dardenne, K.; Polly, R.; Rothe, J.; Hanrath, M.; Reimer, M.; Meerholz, K.; Neudörfl, J.‐M.; Strub, E.; Bruns, J.
Abstract: The preparation of novel technetium oxides, their characterization and the general investigation of technetium chemistry are of significant importance, since fundamental research has so far mainly focused on the group homologues. Whereas the structure chemistry of technetium in strongly oxidizing media is dominated by the Tc O 4 - [ Tc O_ 4]^- anion, our recent investigation yielded the new Tc O 3 N 2 - [ Tc O_ 3 N]^ 2- anion. Brown single crystals of Ba[TcO3 N] were obtained under hydrothermal conditions starting from Ba(OH)2 ⋅ 8H2 O and NH4 [TcO4 ] at 200 °C. Ba [ Tc O 3 N ] Ba[Tc O_ 3 N] crystallizes in the monoclinic crystal system with the space group P 21 / n ( a =7.2159(4) Å, b =7.8536(5) Å, c =7.4931(4) Å and β =104.279(2)°). The crystal structure of Ba [ Tc O 3 N ] Ba[Tc O_ 3 N] consists of isolated Tc O 3 N 2 - [ Tc O_ 3 N]^ 2- tetrahedra, which are surrounded by Ba 2+ cations. XANES measurements complement the oxidation state +VII for technetium and Raman spectroscopic experiments on Ba[TcO3 N] single crystals exhibit characteristic Tc−O and Tc−N vibrational modes. Abstract : Hot chemistry . The nitridotrioxotechnetate anion has been obtained by the reaction of ammonium pertechnetate under highly alkaline conditions. In addition to a single crystal structure analysis, Raman data proves the existence of Tc−O and Tc−N bonds. The oxidation state +VII has further been corroborate by XANES and EXAFS measurements.